Walt Disney's cinderella - Anonymous (Racine : Western Publishing Company, 1986)
With the help of her fairy godmother, a kitchen maid mistreated by her stepmother and stepsisters attends the palace ball where she meets the prince of her dreams.
K
520
K
Keywords: Fairytale; Princess